Assessing the knowledge of medical undergraduates on oral anticoagulation therapy - Chayna Sarkar; Julie B. Wahlang; Reuben P. Syiem; Arky J. Langstieh; Biswadeep Das; Melam Surong (Journal of Family Medicine and Primary Care)
Objective: Oral anticoagulant drugs, such as warfarin, are widely used for preventing and treating vascular and thromboembolic disease in patients with chronic atrial fibrillation, venous thrombosis, and coronary heart disease. As oral anticoagulant therapy has such a narrow therapeutic range, complications in administering these drugs can prove to have a detrimental effect on patients such as life-threatening bleeding might occur. It is therefore necessary to have an adequate knowledge about its actions and its interactions with other dietary factors or any other medication involved. This study was therefore formulated in order to evaluate the knowledge as well as to impart proper awareness to the medical undergraduate students about oral anticoagulation therapy such as to prevent any untoward situation that may arise from the process. Methods: A cross-sectional descriptive study was used to assess the knowledge on oral anticoagulant therapy among the medical undergraduates of a tertiary care hospital. A pre-validated structured questionnaire consisting of 28 questions was adopted, and a separate questionnaire was used for each student. Timing of answering the questionnaire was set at 30 minutes. Scores were evaluated such as a correct answer was given a score of one and wrong answer awarded as zero. Adequate knowledge sore was set above 70% and inadequate knowledge at less than 40%. Results: The response rate was found out to be 67.33% with gender distribution observed to be 71% females and 29% males. From the answers evaluated, overall average score of 67.3 ± 15.9 was obtained indicating that most of the respondents have adequate knowledge about the different mechanism, drug–drug interactions, drug–food interactions, and side effects of anticoagulant therapy, and 100% of the students are well aware about the complications and procedures involved to dissipate information about warfarin therapy. Conclusions: Adequate exposure of students to clinical cases will further help them to focus on the importance of anticoagulation and strengthening their knowledge regarding anticoagulant drug therapy. This will influence the process of physician–patient communication for improving anticoagulation outcome.